The value of Ibn al-'Atiyyah's Qur'anic ınterpretation in the light of method of quotation with poem (Istishhad) - Oğmüş, Harun (SAKARYA UNIV, 2009)
The work on Qur’ânic interpretation called al-Muharrar al-Wajîz fî Tafsîr al-Kitâb al-‘Azîz by Abû Muhammad Abd al-Haqq Ibn Ghâlib Ibn al-Atiyyah al-Ghirnâtî (d. 541/1146), is usually compared with Jar Allah al-Zamahsharî’s al-Kashshaf. Although al-Muharrar is mainly concerned with narrative interpretation, it is one of works which frequently cites poem as evidence (istishhâd). In this article, we shall explore the passages where poems have been quoted as an evidence of a particular meaning for particular word(s) in this work. Besides, it is found out that the most significant source of Ibn al-Atiyyah when he is quoting the poems is Tabârî’s Tafsîr. It is also concluded that Ibn Atiyyathe author of al-Muharrar sometimes makes importants observations and significant analyses about shawâhid, i.e. the poems quoted as way of evidence.
Ibn Atıyye’nin tefsîrinin şiirle istişhad yöntemi açısından değeri
Keywords: Ibn al-Atiyyah; Qur’ânic Interpretation (Tafsîr); Poem; Lexicon; Grammar